Estimation of secondary compounds in Tithonia diversifolia from the regrowth age and primary metabolites - Silva-Déley, M.; Toro, Blanca M.; Verdecia, D. M.; Chacón, E.; Roca, J. A.; Ledea, J. L.; Ramírez, J. L.; Herrera, R. S. (Cuban Journal of Agricultural Science, 2023)
With the objective of determine the effect of regrowth age and the content of primary metabolites (nitrogen, fructose, glucose and sucrose) on the estimation of secondary metabolites in Tithonia diversifolia this study was develop fallowing a random block design with three treatments (60, 120 and 180 days) and six repetitions. For the estimation of this compounds the content of nitrogen (N), glucose (Glu), fructose (Frut), sucrose (Suc) and the plant maturity (age) was evaluated. For the validation the difference between the observed and estimated values was established as well as the relation of them and the variability. For the relation between both values (observed and estimated) when this one is near to unit (1) and to the variability (VC). During the rainy where there were relations between estimated and observed values between 0.84 and 1.39, as well as variation coefficients between 0.01-13 %; the highest values for VC at 60 days were found in total condensed tannins, raffinose and flavonoids (6.96, 8.63 and 8.17 %), 120 days free condensed tannins and saponins (10.88 and 10.18 %), during the dry season the relation values of 0.96 to 1.07 for the studied metabolites, except for verbascose, alkaloids and total steroids which were away from the unit (1) with 0.64, 0.76 and 1.44, respectively. So, it is showed that the estimation of secondary metabolites from the multiple regression lineal models in both seasons of the year, they can be applied as result that regardless to the different criteria that exits about the biochemical paths for the synthesis of them, their precursors will be the primary metabolites because of the dependence of the content of nitrogen, glucose, fructose and sucrose, age and plant phenology. Key words: sugars, mathematical model, nitrogen, estimation, validation